2014
DOI: 10.1111/jhn.12270
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of drop‐out and weight loss success in weight management of obese patients

Abstract: The present study demonstrates that initial weight loss at 1 month made the strongest unique contribution to the prediction of percentage weight loss after 12 months, whereas being married was a negative predictor. Those with a lower educational level and a higher level of obesity were more likely to drop-out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
95
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 41 publications
(49 reference statements)
13
95
1
1
Order By: Relevance
“…The short time of follow-up may have restricted the ability to detect meaningful long-term differences. In this sense, a recent study has detected that the initial body weight loss (at 1 month) is a positive predictor of weight loss after 12 months of intervention [53]. Although the findings of this investigation are based on a population of a nutritional service based on the genetic makeup, the participants included in the study were not necessarily representative of the general population.…”
Section: Discussionmentioning
confidence: 98%
“…The short time of follow-up may have restricted the ability to detect meaningful long-term differences. In this sense, a recent study has detected that the initial body weight loss (at 1 month) is a positive predictor of weight loss after 12 months of intervention [53]. Although the findings of this investigation are based on a population of a nutritional service based on the genetic makeup, the participants included in the study were not necessarily representative of the general population.…”
Section: Discussionmentioning
confidence: 98%
“…Several researchers have previously demonstrated that initial weight loss is associated with study dropout in dietary based weight loss trials [9][10][11][12][13][14][15][16] , however this finding is not consistent and others have found no relationship 11,17,18 . This is the first study to quantify the amount of initial weight loss which predicts dropout and to investigate and quantify additional easily obtainable subject characteristics such as age which can be used to ensure adequate randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…Where a relationship does exist it appears that females may be more likely to drop out than males 2 , although a more recent study has shown that males are more likely to drop out than females 23 . The 2011 systematic review found roughly equal (but small n=4-5) numbers of papers supporting a relationship between high or low initial weight and attrition compared with 18 reporting no relationship more recent papers continue to differ with some supporting the relationship between higher initial weight 18,20 and attrition and some lower initial weight 15 (although no relationship is still the most frequent 9,17,19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low sodium, low protein, and weight loss diets are notoriously difficult to maintain over the long term and the increased water drinking prescription to reduce urinary stone formation and shedding is commonly ignored [4346]. To counter these tendencies, in the current study we offered a palatable diet, relatively simple to prepare, coupled with intense counseling at the outset.…”
Section: Discussionmentioning
confidence: 99%